Using reinforcement algorithms to improve the collaboration efficiency of entrepreneurial teams - Jieqiong Wang; Linghong Jiang (PLoS ONE, 2026)
Entrepreneurial Team (ET) plays an essential role in the business process by driving innovation and optimizing ideas via adaptability, collaboration, and resourcefulness. The team performance is continuously affected because of resource imbalance, poor communication and inefficient task allocation. The importance of ET in organization growth is the main reason for this analysis. Therefore, this work uses Multi-Agent Reinforcement Learning (MARL) to handle efficient dynamic decisions and coordination to improve ET efficiency in dynamic and complex environments. The main intention of this work is to improve resource utilization, communication efficiency and optimize task allocation. During the analysis, Proximal Policy Optimization (PPO) is utilized to direct agents toward achieving collaborative goals. In every state, the agent receives rewards and penalties for their actions, which helps meet the organization’s goal with minimum time and improves the overall task completion rate. This process is evaluated using different case studies like software development, optimized manufacturing and logistic coordination, which helps to validate the system’s adaptability in various scenarios. In addition, different hypotheses are validated via case studies and metrics such as defect resolution, collaboration quality, operational efficiency, resource optimization, and task completion rate. Thus, the work highlights the impact of MARL in ET to ensure the highest performance in a dynamic environment.